ANALISIS STRATEGI PENGEMBANGAN BISNIS UNTUK UMKM BERBASIS TEKNOLOGI INFORMASI DI MASA PANDEMI COVID-19 DI KABUPATEN BANYUWANGI - Endang Purnama Sari; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
Banyuwangi Regency is a city that is rich in human resources and has the potential to develop Information Technology-based Micro, Small and Medium Enterprises (UMKM) products. The purpose of this research is to examine and analyze how the business development strategy for MSMEs Based on Information Technology During the COVID-19 Pandemic in Banyuwangi Regency. The method used in this research is descriptive qualitative and through interviews, observation and documentation using swot analysis to find out strengths, weaknesses, opportunities and threats in developing information technology-based SMEs during the COVID-19 pandemic in Banyuwangi Regency. The informants in this study were the owners of the SH Wholesale store MSMEs, the SH Wholesale store employees, and the SH Wholesale store customers. The results of this study indicate that business actors carry out development strategies, namely product strategies, promotion strategies, pricing strategies, and place strategies to increase sales. and as for the problems faced by business actors using information technology that is less than optimal.Keywords: Development Strategy, MSMEs, Information Technology